Effect of soil physico-chemical properties and plant type on bacterial diversity in semi- arid parts in central Sudan. Part ii. Sharq El-neel region, Khartoum state - Hassan, Hayat; EL-Kamali, Hatil (International Journal of Scientific World, 2016)
Total viable counts of bacteria and bacterial diversity of the different soil samples from three different localities in Sharq EL-Neel region: Soba, AL-Aelafoon and Um Dawan Ban sub-regions were carried out. Soil physical and chemical characteristics (pH, EC,SP,solublecations: Na, K, Ca, Mg and anion P, organic carbon, total nitrogen and soil texture)in each studied sub-regions were measured. Qualitative analysis of microorganisms isolated from the studied soil samples reveal a total of thirteendifferent species of bacteria, of which two are unidentified. The ten species are classified under Bacillus genus. In Sharq EL-Neel regionsoil samples, total bacterial counts ranged from 9.5 × 104 cfu g-1 to 1×103 with a mean of 4×103 cfu g-1. The quantitative data on microbial population recorded in the present study was analysed using two diversity indices. High Shannon-Weiner diversity Index value for bacteria was obtained in AL-Aelfoon sub-region (1.79361), whereas high Simpson's index value was obtained in Um Dawan Ban sub-region (2.80).ActinomycesActinomyces spp. and Streptomyces spp. Where the most abundant microorganisms identified in the three sub-regions. Total bacterial count in Soba soil was positively correlated with pH (r= 0.0194) and sand (r= 0.3205); the total bacterial count in AL-Aelafoon soilwas positively correlated with EC (r= 0.1062), clay (r= 0.3816), silt (r= 0.1936), SP (r= 0.9302), K (r= 0.6252), Ca (r= 0.0015) and Mg (r= 0.1556), whereas the total bacterial count in Um Dawan Ban soil was positively correlated with clay (r= 0.2614), silt (r= 0.0216), SP (r= 0.565), K (r= 0.9645), P (r= 0.0197), Ca (r= 0.7377), Mg (r= 0.0267), N (r= 0.5215) and O.C (r= 0.3214). There were obvious differences in correlation coefficients among the selected criteria (46 % from the total number of correlation coefficients were positively correlated between bacterial counts and soil physico-chemical properties whereas 54% from the total number were positively correlated between plant type and bacterial counts).